Defeasible logic reasoner to support legal reasoning in smart contracts on blockchain - Marković, Marko; Gostojić, Stevan (Frontiers in Blockchain, 2026)
The introduction of information and communication technologies in the legal domain has enabled the automation of some activities in the legal profession. With the advent of blockchain and smart contracts, new tools have emerged for lawyers and their clients, enhancing transparency and increasing trust compared to traditional legal instruments. Once deployed, smart contracts should be able to respond to various events that can occur during the contract’s lifecycle. However, this kind of automation in smart contracts requires them to embed necessary legal knowledge and implement support for legal reasoning. In this paper, we propose a legal reasoning method for smart contracts that incorporates defeasible logic, a key requirement for automated reasoning in the legal domain. The entire reasoning process in our approach is performed on the blockchain infrastructure, making the drawing of conclusions fully transparent and accessible to all interested parties. To demonstrate our concept, we illustrate how certain rights prescribed under labour law can be embedded within a smart contract and deployed on the blockchain as a legal reasoning service. Then, we show how an employment contract can use the reasoning contract to automatically apply legal norms to infer conclusions and determine legal consequences in particular cases. We analyse the benefits and potential issues of this method and discuss directions for future work. Optimisation of the reasoning engine is one of the challenges we identified that needs to be tackled in future.